Нерезонансный усилитель О-типа с наклонным фокусирующим полем - Одаренко, Е. Н.; Шматько, А. А. (Weber Co., 2007)
Multidimensional model of nonresonant millimeter waves amplifier with inclined focusing field is considered. Within the framework of nonlinear self-consistent theory, analysis of the amplifier characteristics for different values of input power and magnetostatic field tilt angle is carried out.
Keywords: нерезонансный усилитель; электронный прибор О-типа; наклонное фокусирующее поле